Multiple eruptive cholesterotic dermatofibromas in a healthy 15-year-old Indian boy - Subhra Dhar; Divya Gupta; Abhishek De (Wolters Kluwer Medknow Publications, 2022)
A 15-year-old healthy boy presented with multiple eruptive brown-colored to hyperpigmented papules all over the body for 1 year. His serum lipids were normal, and HIV serology was negative. Biopsy revealed hyperplastic epidermis along with an ill-defined lesion in the dermis that was composed of spindle-shaped fibroblastic cells and multiple cholesterol clefts within foamy macrophages. A diagnosis of cholesterotic dermatofibroma was made. The case is unusual for the young age of presentation and the presence of multiple eruptive papules.